A Novel Scheme from Compression to Reconstruction for Dynamic MRI Imaging - Gireesh H R, Rangaiah L (International Journal of Advanced Science and Technology, 2020)
Image compression and reconstruction is much vital in today’s smart world of Internet of Things (IoTs). This appears to be a commanding and prevailing tool for transmission, storage and reception of a bunch of images in a variety of applications such as big data, wireless, medical etc. This paper presents a novel scheme from compression to reconstruction for dynamic MRI images. In this work author has worked on the inverse pseudo polar fractional fast Fourier transform (IPPFRFT) and inverse discrete wavelet transform (IDWT) techniques for reconstruction which is extension of segmentation and compression work carried out by author in his previous work in [23]. The pseudo-polar trajectory of PPFRFT technique becomes heir to the various attributes and features of squat sensitivity to the dynamic nature of images. From simulation and comparison results it is very obvious that the proposed work outperforms the existing schemes in terms of both compression and reconstruction from aspects of mean square error, peak signal to noise ratio, structural similarity index measure etc.